Answer:
[tex]3(x - 1)^2 - 11= 0[/tex]
Step-by-step explanation:
Given
[tex]3x^2 - 6x = 8[/tex]
Required
Rewrite in form of [tex]3(x - p)^2 + q = 0[/tex]
[tex]3x^2 - 6x = 8[/tex]
Subtract 8 from both sides
[tex]3x^2 - 6x - 8 = 8 - 8[/tex]
[tex]3x^2 - 6x - 8 = 0[/tex]
Express -8 as 3 - 11;
So, we have:
[tex]3x^2 - 6x + 3 - 11= 0[/tex]
Expand [tex]3x^2 - 6x + 3[/tex]
[tex]3(x^2 - 2x + 1) - 11= 0[/tex]
Factorize the expression in the bracket;
[tex]3(x^2 - x -x + 1) - 11= 0[/tex]
[tex]3(x(x - 1) -1(x - 1)) - 11= 0[/tex]
[tex]3((x - 1)^2) - 11= 0[/tex]
[tex]3(x - 1)^2 - 11= 0[/tex]
By comparison: [tex]3(x - p)^2 + q = 0[/tex]
[tex]p= 1[/tex]
[tex]q = -11[/tex]